Advances in Oxosulfonylation Reaction. Issue 21 (14th September 2020) - Ghosh, Sumit; Samanta, Sadhanendu; Ghosh, Asim Kumar; Neogi, Sukanya; Hajra, Alakananda
Abstract: Oxosulfonylation is a difunctionalization protocol where oxo and sulfonyl groups are introduced in one step to construct ketosulfones and N ‐acylsulfonamides from simple and readily accessible reagents. The development of oxosulfonylation methods has gained significant attention due to their importance in organic and medicinal chemistry. This review article provides a brief and concise overview of the current status and latest methodologies using green oxidant and sulfonyl sources for oxosulfonylation reactions developed in the last two decades. Abstract :